Two key arginine residues in the coat protein of Bamboo mosaic virus differentially affect the accumulation of viral genomic and subgenomic RNAs - Hung, Chien-Jen; Hu, Chung-Chi; Lin, Na-Sheng; Lee, Ya-Chien; Meng, Menghsiao; Tsai, Ching-Hsiu; Hsu, Yau-Heiu (Molecular plant pathology, 2014)
Summary The interactions between viral RNAs and coat proteins (CPs) are critical for the efficient completion of infection cycles of RNA viruses. However, the specificity of the interactions between CPs and genomic or subgenomic RNAs remains poorly understood. In this study, Bamboo mosaic virus (BaMV) was used to analyse such interactions. Using reversible formaldehyde cross‐linking and mass spectrometry, two regions in CP, each containing a basic amino acid (R99 and R227, respectively), were identified to bind directly to the 5′ untranslated region of BaMV genomic RNA. Analyses of the alanine mutations of R99 and R227 revealed that the secondary structures of CP were not affected significantly, whereas the accumulation of BaMV genomic, but not subgenomic, RNA was severely decreased at 24 h post‐inoculation in the inoculated protoplasts. In the absence of CP, the accumulation levels of genomic and subgenomic RNAs were decreased to 1.1%–1.5% and 33%–40% of that of the wild‐type (wt), respectively, in inoculated leaves at 5 days post‐inoculation (dpi). In contrast, in the presence of mutant CPs, the genomic RNAs remained about 1% of that of wt, whereas the subgenomic RNAs accumulated to at least 87%, suggesting that CP might increase the accumulation of subgenomic RNAs. The mutations also restricted viral movement and virion formation in Nicotiana benthamiana leaves at 5 dpi. These results demonstrate that R99 and R227 of CP play crucial roles in the accumulation, movement and virion formation of BaMV RNAs, and indicate that genomic and subgenomic RNAs interact differently with BaMV CP.